The Effect of Slow Stroke Back Massage On Intensity of Pain In Elderly With Rheumatic Arthritis - Wilda, Lexy Oktora; Nasoka, Moch Dhian (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Elderly who experience rheumatic generally complain of pain which has an impact on decreasing the productivity of life in the elderly. The research design was a pre experimental design with the One Group Pretest-Posttest Design approach. Population of 35 people. The sampling method uses total sampling. Analysis used the Wilcoxon test with α = 0.05. Showed that of the 35 respondents before being given the Slow Stroke Back Massage, most of them had moderate pain levels, namely 18 respondents (51.4%). After being given a slow stroke back massage, most of them had a mild pain level, namely 19 respondents (54.3%). The Wilcoxon test results show p-value = 0,000 ≤ a = 0.05, Slow stroke back massage therapy only acts as a supportive therapy and does not replace the role of pharmacological therapy. Collaboration with doctors is needed in providing pain relievers or other supportive therapies.